2017
DOI: 10.1128/aac.02707-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibiofilm Activity of Eucarobustol E against Candida albicans

Abstract: Formyl-phloroglucinol meroterpenoids (FPMs) are important types of natural products with various bioactivities. Our antifungal susceptibility assay showed that one of the Eucalyptus robusta-derived FPMs, eucarobustol E (EE), exerted a strong inhibitory effect against Candida albicans biofilms at a concentration of 16 g/ml. EE was found to block the yeast-to-hypha transition and reduce the cellular surface hydrophobicity of the biofilm cells. RNA sequencing and real-time reverse transcription-PCR analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 80 publications
(111 reference statements)
0
38
0
Order By: Relevance
“…The MIC 80 values of KPA against different Candida species were measured by the broth microdilution method. The results showed that KPA exerted a moderate antifungal effect (based on the previous reports [6,10,13,17]) against the five most common Candida species, including C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and C. krusei, the MIC 80 value of which was all 16 μg/mL. The MIC 80 values of the positive control AMB were 0.5 or 1 μg/mL, respectively ( Table 1).…”
Section: Antifungal Activity Of Kpa On Candida Species (Mics)mentioning
confidence: 58%
“…The MIC 80 values of KPA against different Candida species were measured by the broth microdilution method. The results showed that KPA exerted a moderate antifungal effect (based on the previous reports [6,10,13,17]) against the five most common Candida species, including C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and C. krusei, the MIC 80 value of which was all 16 μg/mL. The MIC 80 values of the positive control AMB were 0.5 or 1 μg/mL, respectively ( Table 1).…”
Section: Antifungal Activity Of Kpa On Candida Species (Mics)mentioning
confidence: 58%
“…For example, mixed polymicrobial infections due to the presence of bacteria and pathogenic fungi, commonly found in patients with chronic infections, constitute a noteworthy health care burden. Citrus EOs are capable of preventing the polymicrobial biofilm formed by Pseudomonas aeruginosa and pathogenic fungi, in particular A. fumigatus and Scedosporium apiospermum , at concentration between 50 mg/L and 250 mg/L [ 120 ].These EOs showed a potential of inhibiting fungal growth with MIC in concentrations of 50 mg/L and 250 mg/L. Furthermore, Citrus EOs impeded formation of bacterial and fungal monomicrobial biofilms in concentrations of 50 mg/L.…”
Section: Essential Oils and Biofilmsmentioning
confidence: 99%
“…Our previous research also demonstrated that several novel FPMs exerted antifungal and antibiofilm activities against Candida spp. (Liu R. H. et al, 2017). Further investigations on FPMs showed that those FPMs with weak or without antifungal effects demonstrated enhanced activities when combined with other antifungal FPMs or azoles (data not shown).…”
Section: Introductionmentioning
confidence: 99%